Novel analytical solutions of stochastic Ginzburg-Landau equation driven by Wiener process via the improved modified extended tanh function method - Alhojilan, Yazid; Ahmed, Hamdy M. (Alexandria engineering journal, 2023)
In this manuscript, the improved modified extended tanh integration technique is implemented to investigate the exact solutions of stochastic Ginzburg–Landau model driven by Wiener process which appeared in various fields of chemistry, mathematics and physics. Many types of stochastic wave solutions are raised such as hyperbolic stochastic solutions, trigonometric stochastic solutions, Weierstrass elliptic stochastic solutions and Jacobi elliptic stochastic solutions. Moreover, 3D and 2D graphical representations are depicted to show the effect of the multiplicative noise on the propagated waves. The results reveal that as the noise level increases, the wave degrades. The wave is distorted when σ⩾1. In addition, the 3D graphical representation show that the propagated wave is flattered when the noise strength is increased. These solutions may be applicable in various applications in applied science. The proposed method is efficient, direct and powerful.